Joseph Smith, Jr.: reappraisals after two centuries - Neilson, Reid Larkin; Givens, Terryl (Oxford University Press, 2009)
Mormon founder Joseph Smith is one of the most controversial figures of 19th century American history, and a virtually inexhaustible subject for analysis. In this volume, 15 scholars offer essays on how to interpret and understand Smith and his legacy.